TiF4 and NaF varnishes as anti-erosive agents on enamel and dentin erosion progression in vitro - Livia Picchi COMAR; Cristiane de Almeida Baldini CARDOSO; Senda CHARONE; Larissa Tercilia GRIZZO; Marília Afonso Rabelo BUZALAF; Ana Carolina MAGALHÃES (University of São Paulo, 2015)
Objective This study assessed the effect of fluoride varnishes on the progression of tooth erosion in vitro. Material and Methods: Forty-eight enamel and 60 root dentin samples were previously demineralized (0.1% citric acid, pH 2.5, 30 min), leading to a baseline and erosive wear of 12.9 and 11.4 µm, respectively. The samples were randomly treated (6 h) with a 4% TiF4 varnish (2.45%F-, pH 1.0), a 5.42% NaF varnish (2.45%F-, pH 5.0), a placebo varnish and no varnish (control). The samples were then subjected to erosive pH cycles (4x90 s/day in 0.1% citric acid, intercalated with artificial saliva) for 5 days. The increment of the erosive tooth wear was calculated. In the case of dentin, this final measurement was done with and without the demineralized organic matrix (DOM). Enamel and dentin data were analyzed using ANOVA/Tukey's and Kruskal-Wallis/Dunn tests, respectively (p<0.05). Results The TiF4 (mean±s.d: 1.5±1.1 µm) and NaF (2.1±1.7 µm) varnishes significantly reduced enamel wear progression compared to the placebo varnish (3.9±1.1 µm) and control (4.5±0.9 µm). The same differences were found for dentin in the presence and absence of the DOM, respectively: TiF4 (average: 0.97/1.87 µm), NaF (1.03/2.13 µm), placebo varnish (3.53/4.47 µm) and control (3.53/4.36 µm). Conclusion The TiF4 and NaF varnishes were equally effective in reducing the progression of tooth erosion in vitro.